Seismic Response of Isolated Buildings with Adding SMA-Based Recentering Damping Devices and Rotation Friction Dampers (Damascus University Journal for engineering sciences, 2023)
The effect of ground motions in building might be decreased by adding the seismic isolation system.In buildings that are isolated by this system of isolation, it should be getting back to their initial place by controlling the deformations and displacements especially peak deformations and it should have the possibility to restore the deformations. Civil engineering has lots of smart materials that may handle this case optimally and behave very well in a range of engineering applications, like shape memory alloy (SMA). These materials have several properties such as superelastic characteristics and the effects of shape memory.This paper compares the effectiveness of the friction-viscoelastic dampers (FD) with that of the re-centering SMAs by conducting Nonlinear Time History analysis to an isolated reinforced concrete building with different three heights (eight, twelve, and sixteen stories), considering two cases: the first case is base isolation system (lead Rubber Bearings LRB+ Flat Sliding Bearing FSB) with additional Rotation Fiction Damper FD, and the second case is base isolation system (LRB+FSB) with additional Re-SMAs. The periods, displacements, and shear forces distribution considering different building height for each system are compared.The results show a significant improvement in the building performance by using recentering (SMAs) with isolation system in terms of reducing Displacements (on average 7%) and Drift (on average 16%) compared to the use of FD, with increasing building’s heights, it restored successfully the building to the original place after the ground motion. Also, using the characteristics of the recentering damping devices SMAs is efficient for decreasing displacement and lateral deformation in the level of the isolator, and this will help in reserving isolation efficacy and protecting the superstructure when increasing the elasticity of the structure.
Keywords: Seismic isolation; Shape memory alloys; Super elasticity; Friction- dampers; Smart Material; Recentering; Residual displacement; Drift